The emerging role of anoctamin-1 in cardiac and cerebrovascular diseases - Zhang, Jia-qi; Wen, Zeng-jin; Han, Xiao-hua; Qiu, Zhen-kang; Yang, Qing-ya; Qiu, Yue (Frontiers in Cardiovascular Medicine, 2025)
Cardiocerebral vascular disease has long been the leading cause of morbidity and mortality worldwide. Although there are many effective avenues for preventing and treating cardiocerebral vascular disease, further research is still needed to identify more novel molecular targets for therapeutic intervention. Anoctamin-1 (ANO1), also known as transmembrane protein 16A (TMEM16A), is the molecular identity of calcium-activated chloride channels (CaCCs) and is widely distributed in myocardial cells and the vasculature, including but not limited to the thoracic aorta, mesenteric artery, cerebral artery, and portal vein. ANO1 has many functions in the cardiocerebral vascular system, including cardiac excitability, vascular smooth muscle contraction, and epithelial cell secretion. Aberrant expression or dysfunction of ANO1 is associated with several cardiocerebral vascular diseases, including myocardial ischaemia/reperfusion injury (MIRI), arrhythmias, cardiac fibrosis, hypertension, and stroke. Therefore, this review provides an overview of ANO1, including its structure, distribution, and activation mechanism, and highlights the current knowledge of ANO1 in the pathophysiological process of heart diseases, hypertension, and stroke. We also summarise the pharmacological regulatory target of ANO1, providing promising insights for applying ANO1 inhibitors as cardiac and cerebrovascular therapeutic agents.